2011
DOI: 10.1063/1.3598400
|View full text |Cite
|
Sign up to set email alerts
|

In situ compression study of taper-free metallic glass nanopillars

Abstract: Because tapering leads to inevitable artifacts in the analyses of compression experiments on micrometer sized pillars, in this study taper-free nanosized pillars of Zr-based metallic glass of Zr 61.8 Cu 18 Ni 10.2 Al 10 composition with diameter ranging from 600 to 90 nm were fabricated. These pillars were compressed in situ in a transmission electron microscope as a function of pillar diameter. Under compression each pillar of large diameter exhibits predominant inhomogeneous and intermittent plastic flow cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Obviously, for pillars with smaller enough size, the Cu-Zr-Al MG exhibited very good plastic deformability. Similar phenomena were reported later in other works [10,22,[28][29][30][31][32] However, a close examination on these works is ready to find that all the tested samples had a tapered geometry which will undoubtedly generate stress/strain gradient with their magnitude determined by the taper angle and the initial top diameter. [45] Therefore, it had been argued that the observed plastic behavior of MGs during the compression tests might stem from the tapered sample geometry and the imperfect contact interface.…”
Section: Strength-size Relationshipmentioning
confidence: 67%
See 1 more Smart Citation
“…Obviously, for pillars with smaller enough size, the Cu-Zr-Al MG exhibited very good plastic deformability. Similar phenomena were reported later in other works [10,22,[28][29][30][31][32] However, a close examination on these works is ready to find that all the tested samples had a tapered geometry which will undoubtedly generate stress/strain gradient with their magnitude determined by the taper angle and the initial top diameter. [45] Therefore, it had been argued that the observed plastic behavior of MGs during the compression tests might stem from the tapered sample geometry and the imperfect contact interface.…”
Section: Strength-size Relationshipmentioning
confidence: 67%
“…[14], [20], and [21] respectively. [29] Zr-based Compression Independence 90 nm − 600 nm Chen et al [21] [30] Cu-based Compression Independence 70 nm − 645 nm Kuzmin et al [31,32] Al-based Compression Independence 110 nm − 900 nm The literature strength data used in this plot are all for samples that exhibited shear banding as the controlling mode for yielding. [22] Compared to crystalline materials, MGs have superior elastic limit.…”
Section: Strength-size Relationshipmentioning
confidence: 99%
“…Although the slight tapering still causes the deformation starting from the top and proceeding towards the base, a shear band (SB) generally traverses through the pillar without constraint at either the leading or the rear front. A taper-free nanopillars has been cutted by De Hosson et al using a combination of top and side focused ion beam (FIB) milling [25][26][27][28]. They found that the key features of the fabrication must be tilted to enable milling of the pillar sideways avoiding tapering and the FIB current can be reduced step by step in order to mill until the desired size with damage-free surface is obtained by Ga ions.…”
Section: Resultsmentioning
confidence: 98%
“…In order to investigate plasticity mechanisms at the nanometer-scale, AFM indentation experiments were performed with varying maximal loads and varying loading rates. We discuss our results with regard to dislocation activity in crystalline materials and to the recent discussion of plasticity mechanisms in metallic glasses, including the generation of shear bands and their incipient size and indentation size effects down to the structural length scale of metallic glasses [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%